CXCR1 and its downstream NF-κB inflammation signaling pathway as a key target of Guanxinning injection for myocardial ischemia/reperfusion injury - Xiao, Guangxu; Liu, Jiaxu; Wang, Huanyi; He, Shuang; Liu, Jianwei; Fan, Guanwei; Lyu, Ming; Zhu, Yan (Frontiers in Immunology, 2022)
Guanxinning Injection (GXNI) is used clinically to treat cardiac injury, but its active components and mode of action remains unclear. Therefore, a myocardial ischemia-reperfusion injury (MIRI) model-based integrated strategy including function evaluation, RNA-seq analysis, molecular docking, and cellular thermal shift assay (CETSA) was employed to elucidate the effect and mechanism of GXNI and its main ingredient on cardiac injury. These results revealed that GXNI significantly improved cardiac dysfunction and myocardial injury in I/R mice. RNA-seq analysis clarified that CXCR1-mediated interleukin-8 pathway played a critical role in MIRI. Molecular docking screening identified danshensu (DSS) as the major active components of GXNI targeting CXCR1 protein, which was confirmed in an oxygen-glucose deprivation/reoxygenation-induced cardiomyocytes damage model showing that GXNI and DSS reduced the protein expression of CXCR1 and its downstream NF-κB, COX-2, ICAM-1 and VCAM-1. CETSA and isothermal dose-response fingerprint curves confirmed that DSS combined with CXCR1 in a dose-dependent manner. Furthermore, GXNI and DSS significantly decreased the expression levels of IL-6, IL-1β and TNF-α and the number of neutrophils in post I/R myocardial tissue. In conclusion, this study revealed that GXNI and its active components DSS exert inhibitory effects on inflammatory factor release and leukocyte infiltration to improve I/R-induced myocardial injury by down-regulating CXCR1-NF-κB-COX-2/ICAM-1/VCAM-1 pathway.